Overzealous over-the-counter cough syrup ingestion leading to serious manifestation in a child – A case report - Dinkar Yadav; Hunny Verma; Neha Yadav; Kapil Bhalla (Journal of Family Medicine and Primary Care)
Cough is a protective reflex that allows clearance of secretions from upper respiratory tract. It is not a disease by itself but a symptom of underlying disease. In a majority of cases, it is self-limiting and requires only supportive care. But over-the-counter cough syrups are inadvertently used to relieve cough in Indian settings. We hereby report a case of a 6-year-old girl child who presented to pediatrics emergency services with complaints of loss of consciousness and abnormal body movement after ingestion of dextromethorphan and chlorpheniramine containing cough syrup. All investigations including cerebrospinal fluid examination, neuroimaging, and electroencephalogram revealed no significant abnormality. The child was admitted for 5 days and discharged after that in stable conditions.